Modeling the process of ensuring the financial security of enterprise - Sylkin, O.; Arestenko, Tetiana; Арестенко, Тетяна Вікторівна; Арестенко, Татьяна Викторовна (My University, 2021)
Today, the engineering industry in Ukraine is characterized by a crisis development, formed due to the fact that domestic enterprises can operate in such political and economic conditions, which are characterized by significant instability. The last five years have been extremely difficult for the Ukrainian economy, and all the events taking place in the country (depreciation of the hryvnia, hostilities, loss of the Russian market) have a very acute impact on the financial security of domestic enterprises. So, the issues of diagnosing the crisis state of mechanical engineering enterprises are very relevant today, since a large number of existing models and methods were simply not formed for the Ukrainian reality
Keywords: security; financial security; enterprise; model